Deposit of victim and witness testimony in the criminal procedure of The Republic Of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
Based on the analysis of the novelty in the criminal-procedural legislation of Kazakhstan, the author discusses peculiarities and issues related to examination of a victim and witness by investigating judge (testimony deposit). The analysis of foreign criminal procedure legislation on the use of indications of deposit.Key words: evidence criminal process, victim and witness testimony, deposit, investigating judge, reception of right.